WASTEWATER TREATMENT DESIGN OF KAMPAR STATE POLYTECHNIC CPO PURIFICATION LABORATORY - sri Murda Niati; Idha Silvi; Endang Supraptiah; Gemala Cahya (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
Kampar Polytechnic has a miniplan laboratory for processing CPO into cooking oil, biodiesel, and soap. During its operation, this processing produces liquid waste and solid waste. The waste released must be treated before being discharged into the environment, provided that the amount of COD reduction efficiency is good enough (63,41%). The COD content in wastewater is still above environmental quality standards. To reduce COD according to permissible standards, recycling is carried out with effluent from the sedimentation process returned to the equalization unit. The design of equalization, coagulation, and flocculation tubs has been successfully carried out. The results obtained are the dimensions of the equalization bath at 2m length, 2m width, and 1.2m height. The dimensions of the coagulation bath are 1.5m long, 1.0m wide, and 1.2m high. The dimensions of the flocculation bath are 2.5m long, 1.5m wide, and 1.2m high, with the provision that consideration meets the volume of liquid waste treated.